2022
DOI: 10.4274/mirt.galenos.2021.85530
|View full text |Cite
|
Sign up to set email alerts
|

Use of YouTube as an Information Source for Radioactive Iodine Therapy: Do YouTube Videos Have High Quality?

Abstract: Objectives: Radioactive iodine (RAI) therapy is a radionuclide treatment for hyperthyroidism and well-differentiated thyroid cancer. One of the most popular sources of information for patients on the internet is YouTube. This study aimed to examine the quality of videos about RAI treatment. Methods: This cross-sectional study was performed by using videos in YouTube. The terms “radyoaktif iyot tedavisi” and “radioactive iodine treatment” were used to search related vide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 17 publications
1
7
0
Order By: Relevance
“…For this purpose, content of medical videos may be evaluated with any of the parameters of JAMA, GQS and DISCERN. Studies have reported that there is a high positive correlation between these three parameters (18)(19)(20). In our study, significant positive correlations were found between JAMA score, GQS score, and DISCERN score.…”
Section: Discussionsupporting
confidence: 71%
See 2 more Smart Citations
“…For this purpose, content of medical videos may be evaluated with any of the parameters of JAMA, GQS and DISCERN. Studies have reported that there is a high positive correlation between these three parameters (18)(19)(20). In our study, significant positive correlations were found between JAMA score, GQS score, and DISCERN score.…”
Section: Discussionsupporting
confidence: 71%
“…In another study of Şan (19), YouTube videos related to 'radioactive iodine treatment' were evaluated. Similar to our study, the average number of comments, annual number of comments, number of likes, number of views, and VPI values of physician sourced videos were found to be lower than non-physician sourced videos.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Also, we could not find a significant difference between educational and personal videos in terms of average duration, number of views, and number of comments. However, in the available literature, it has been reported that educational videos are generally of higher quality and almost always lower quality videos are more popular [ 16 , 19 , 20 , 22 , 24 , 30 , 36 , 40 ]. The only exception we could find is Duran et al‘s study on prostate cancer videos, in which no significant relationship was found between the quality markers (JAMA and GQS scores) and likes, comments, views, and VPI [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…Topics of cancer-related videos that are studied are colorectal, bladder, prostate, pancreatic, oral, skin, cervical, larynx, thyroid, anal, breast, gynecological, and testicular cancer [15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34]. Besides these, glioblastoma treatment, cancer-related pain management, pediatric cancer clinical Fig.…”
Section: Discussionmentioning
confidence: 99%